Six-Year Follow-Up of Fractional Flow Reserve-Guided Versus Angiography-Guided Coronary Artery Bypass Graft Surgery. (June 2018) - Fournier, Stephane; Toth, Gabor G.; De Bruyne, Bernard; Johnson, Nils P.; Ciccarelli, Giovanni; Xaplanteris, Panagiotis; Milkas, Anastasios; Strisciuglio, Teresa; Bartunek, Jozef; Vanderheyden, Marc; Wyffels, Eric; Casselman, Filip; et al.
Abstract : Background—: Fractional flow reserve (FFR)-guided coronary artery bypass graft (CABG) surgery has been associated with lower number of graft anastomoses, lower rate of on-pump surgery, and higher graft patency rate as compared with angiography-guided CABG surgery. However, no clinical benefit has been reported to date. Methods and Results—: Consecutive patients (n=627) treated by CABG between 2006 and 2010 were retrospectively included. In 198 patients, at least 1 stenosis was grafted according to FFR (FFR-guided group), whereas in 429 patients all stenoses were grafted based on angiography (angiography-guided group). The 2 coprimary end points were overall death or myocardial infarction and major adverse cardiovascular events (composite of overall death, myocardial infarction, and target vessel revascularization) up to 6-year follow-up. In the FFR-guided group, patients were significantly younger (66 [57–73] versus 70 [63–76]; P <0.001), more often male (82% versus 72%; P =0.008), and less often diabetic (21% versus 30%; P =0.023). Clinical follow-up (median, 85 [66–104] months) was analyzed in 396 patients after 1:1 propensity-score matching for these 3 variables. The rate of overall death or myocardial infarction was significantly lower in the FFR-guided (n=31 [16%] versus n=49 [25%]; hazard ratio, 0.59 [95% confidence interval, 0.38–0.93]; P =0.020) as compared with the angiography-guided group. Major adverse cardiovascular events rate was also numerically lower in the FFR-guided than in the angiography-guided group (n=42 [21%] versus n=52 [26%]; hazard ratio, 0.77 [95% confidence interval, 0.51–1.16]; P =0.21). Conclusions—: FFR-guided CABG is associated with a significant reduction in the rate of overall death or myocardial infarction at 6-year follow-up as compared with angiography-guided CABG. Abstract : Supplemental Digital Content is available in the text.